Intranuclear differences in calmodulin gene expression in the trigeminal nuclei of the rat brain - Bakota Lídia (Acta biologica Szegediensis, 2005)
The expression patterns of the three CaM genes were quantitatively localized by using in situ hybridization techniques to detect gene-specific [35S]-labeled cRNA probes complementary to the multiple CaM mRNAs in the trigeminal nuclei of the adult rat brain. The three distinct CaM genes were widely expressed throughout the midbrain-brain stem area with moderate intensities. In general, mRNAs transcribed from the CaM III gene were the most abundant, followed by the CaM I and CaM II mRNA populations. Moreover, significant differences in the amounts of the transcripts of some CaM genes were found between the rostral and caudal parts of the individual nuclei of the trigeminal system. In most cases, the CaM gene-specific transcripts displayed a clear differential distribution along the rostrocaudal axis: they were more abundant in the rostral parts of these nuclei. For example, the levels of mRNAs transcribed from each of the CaM I, II and III genes were significantly higher in the rostral part of the principal sensory trigeminal nucleus, while the rostral part of the motor trigeminal nucleus exhibited an elevated amount of transcripts for the CaM I gene only. Interestingly, the CaM II mRNAs were most abundant in the caudal part of the mesencephalic trigeminal nucleus. Moreover, the largest difference between any of the CaM gene-specific transcript contents of the rostral and caudal parts was found for those of the CaM II gene in the principal sensory trigeminal nucleus. Here, the intranuclear difference was about 50%, the rostral part being the richer in CaM II mRNAs. Our results draw attention to the possible causal relation between the differences in the neuronal circuitry of the rostral and caudal parts of these nuclei and their differential CaM gene expression. This somatotopy may have important functional implications.